1997
DOI: 10.1007/bf02385906
|View full text |Cite
|
Sign up to set email alerts
|

Effects of granulocyte colony-stimulating factor on bacterial translocation due to burn wound sepsis

Abstract: The presence of certain defects in both cellular and humoral immunity after thermal injury has been established. Likewise, the translocation of enteric bacteria to the mesenteric lymph nodes and to distant organs has also been observed following serious thermal injury. The effects of granulocyte colony-stimulating factor (G-CSF) on bacterial translocation, the small bowel mucosa, and cecal bacterial content were investigated in a rat model of burn wound sepsis in which albino Wistar rats were scalded over 30% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…Therefore, we suggest that the ability of immunonutrition to prevent BT is probably related to improvement of host immunity. Our finding supports many other studies which have shown that BT was prevented without improvement in intestinal mucosal barrier [38][39][40]. In a rat model of burn wound sepsis, Yalcin et al [38] reported that both the control and granulocyte colony-stimulating factor (g-csf) treated rats had disrupted mucosal barrier manifested with blunted villae in distal ileum.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Therefore, we suggest that the ability of immunonutrition to prevent BT is probably related to improvement of host immunity. Our finding supports many other studies which have shown that BT was prevented without improvement in intestinal mucosal barrier [38][39][40]. In a rat model of burn wound sepsis, Yalcin et al [38] reported that both the control and granulocyte colony-stimulating factor (g-csf) treated rats had disrupted mucosal barrier manifested with blunted villae in distal ileum.…”
Section: Discussionsupporting
confidence: 80%
“…Our finding supports many other studies which have shown that BT was prevented without improvement in intestinal mucosal barrier [38][39][40]. In a rat model of burn wound sepsis, Yalcin et al [38] reported that both the control and granulocyte colony-stimulating factor (g-csf) treated rats had disrupted mucosal barrier manifested with blunted villae in distal ileum. They demonstrated that although no improvement was seen in the mucosal barrier in g-csftreated rats bacterial translocation was significantly decreased.…”
Section: Discussionsupporting
confidence: 80%
“…Full thickness burn injury is induced in all rats according to the methods of Walker and Yalcin [17,18]. In this method, rats are anesthetized, and hair on the back of each rat is removed with an electric clipper.…”
Section: Full Thickness Burn Wound Modelmentioning
confidence: 99%
“…In this model, approximately 30% of the total body surface area of a mouse was burned by exposure to a flame for 10 s followed by inoculation with Pseudomonas aeruginosa . This procedure was modified by Rumbaugh et al and others to create a burn wound by use of scalding water (90°C) rather than open flame [52] and also applied to rats [53]. The dorsal cutaneous burn wound models have been used to explore pathogen quorum sensing [52], bacterial migration and development of sepsis from infected burn wounds [29], and different therapies [5456].…”
Section: 0 Infected Cutaneous Defectsmentioning
confidence: 99%